Plasma and Field Observations in the Magnetospheric Source Region of a Stable Auroral Red (SAR) Arc by the Arase Satellite on 28 March 2017. Issue 10 (1st October 2020) - Inaba, Yudai; Shiokawa, Kazuo; Oyama, Shin‐ichiro; Otsuka, Yuichi; Oksanen, Arto; Shinbori, Atsuki; Gololobov, Artem Yu; Miyoshi, Yoshizumi; Kazama, Yoichi; Wang, Shiang‐Yu; Tam, Sunny W. Y.; Chang, Tzu‐Fang; et al.
Abstract: A stable auroral red (SAR) arc is an aurora with a dominant 630 nm emission at subauroral latitudes. SAR arcs have been considered to occur due to the spatial overlap between the plasmasphere and the ring‐current ions. In the overlap region, plasmaspheric electrons are heated by ring‐current ions or plasma waves, and their energy is then transferred down to the ionosphere where it causes oxygen red emission. However, there have been no study conducted so far that quantitatively examined plasma and electromagnetic fields in the magnetosphere associated with SAR arc. In this paper, we report the first quantitative evaluation of conjugate measurements of a SAR arc observed at 2204 UT on 28 March 2017 and investigate its source region using an all‐sky imager at Nyrölä (magnetic latitude: 59.4°N), Finland, and the Arase satellite. The Arase observation shows that the SAR arc appeared in the overlap region between a plasmaspheric plume and the ring‐current ions and that electromagnetic ion cyclotron waves and kinetic Alfven waves were not observed above the SAR arc. The SAR arc was located at the ionospheric trough minimum identified from a total electron content map obtained by the GNSS receiver network. The Swarm satellite flying in the ionosphere also passed the SAR arc at ~2320 UT and observed a decrease in electron density and an increase in electron temperature during the SAR‐arc crossing. These observations suggest that the heating of plasmaspheric electrons via Coulomb collision with ring‐current ions is the most plausible mechanism for the SAR‐arc generation. Plain Language Summary: A stable auroral red (SAR) arc is an aurora with an optical red emission at latitudes slightly lower than the auroral zone. SAR arcs have been considered to occur due to the spatial overlap between the low‐energy plasmaspheric electrons and the high‐energy ring‐current ions. In the overlap region, plasmaspheric electrons are heated by ring‐current ions or plasma waves, and their energy is then transferred down to the upper atmosphere to cause the red emission. However, there have been no study conducted so far that quantitatively examined plasma and electromagnetic fields in the magnetospheric source region of SAR arcs. In this paper, we report the first quantitative evaluation of a SAR arc using an all‐sky imager at Nyrölä, Finland, and the Arase satellite. The Arase observation shows that the SAR arc appeared in the overlap region between a plasmaspheric plume and the ring‐current ions in the inner magnetosphere. The electromagnetic waves associated with the SAR arc were not observed. These observations suggest that the heating of plasmaspheric electrons by ring‐current ions is the most plausible mechanism for the SAR‐arc generation. This result provides direct evidence of the previous theoretical expectation on the generation mechanism of red aurora at lower latitudes. Key Points: The conjugate measurements of a detached SAR arc on 28 March 2017 are analyzed using observations from the Arase satellite Swarm and GNSS‐TEC data show that the electron density decreased and the electron temperature increased in the ionosphere above the SAR arc The observed plasmas and electromagnetic fields suggest that Coulomb collision is the most plausible mechanism for the SAR‐arc generation